Harmonization of regulations and innovation: VR/AR teacher readiness model in Indonesian education under public policy based on Pancasila - Helga Charolina Antonia Silubun; Dadan Rosana; Samsul Hadi (Indonesian Journal of Electrical Engineering and Computer Science, 2026)
The adoption of immersive technologies such as virtual reality (VR) and augmented reality (AR) faces the challenge of significant infrastructure disparities between developed countries (HIC) and developing countries (LMIC). In Indonesia, this implementation is hampered by an acute digital divide and the absence of an adaptive regulatory framework. This research proposes Pancasila-driven VR/AR educational architecture (PD-VAREA), a multidimensional framework that integrates principles of social justice into technical optimization through edge computing and adaptive rendering. The novelty of this research lies in the formalization of the teacher readiness index (Tready) using an integral calculus approach to predict systemic readiness. Numerical simulation results show that the PD-VAREA model produces a Tready value of 2.4 (High Readiness), far exceeding the conventional market-driven model, which reaches 0.6. These findings prove that the integration of cost-effective technology (frugal technology) with public policies based on the Fifth Principle of Pancasila is able to emphasize network latency below 20 ms while ensuring equitable access. This article provides a contribution in the form of a predictive model and strategic recommendations for policymakers in LMIC to mitigate the risks of digital inequality in the global education transformation.